(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
As a result of studying special basic knowledge of design, students develop creativity. In the course of education, knowledge belonging to the national culture of the Uzbek people is presented to students in a systematic way. Creativity in design requires relative independence. This independence is manifested through clearly implemented functions. Creative independence is manifested in connection with the field of professional activity and the field of personal interests.